Characterizations and comparison of low sulfur fuel oils compliant with 2020 global sulfur cap regulation for international shipping - Nelson, R.K.; Scarlett, Alan; Gagnon, Monique; Holman, Alex; Reddy, C.M.; Sutton, P.A.; Grice, Kliti (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
The International Marine Organization 2020 Global Sulfur Cap requires ships to burn fuels with <0.50% S and some countries require <0.10% S in certain Sulfur Emission Control Areas but little is known about these new types of fuels. Using both traditional GC–MS and more advanced chromatographic and mass spectrometry techniques, plus stable isotopic, δ13C and δ2H, analyses of pristane, phytane and n-alkanes, the organic components of a suite of three 0.50% S and three 0.10% S compliant fuels were characterized. Two oils were found to be near identical but all of the remaining oils could be forensically distinguished by comparison of their molecular biomarkers and by the profiles of the heterocyclic parent and alkylated homologues. Oils could also be differentiated by their δ13C and δ2H of n-alkanes and isoprenoids. This study provides important forensic data that may prove invaluable in the event of future oil spills.